(untitled) (LSP International Journal, 2024)
Reviews from prior research indicated that in EFL classrooms, teachers have a tendency to favor lower-level questions over higher-level ones. Therefore, this case study primarily aims to examine the types of questions proposed by Chinese college EFL teachers and the impact of teacher’s questioning techniques on the cultivation and engagement of students’ higher-order thinking skills. The current qualitative study utilized classroom observations to collect data regarding teacher’s questioning. The data collected from class observations were anlyzed using content analysis both in quantitative and qualitative way. The results of this study indicated that the participating teachers posed a higher percentage of lower-level cognitive questions than higher-level ones. The study also revealed weaknesses in the responding teachers’ questioning skills that could foster students’ higher order thinking. The findings are attributed to a lack of professional knowledge of HOTS instruction and the rigid curricula. Furthermore, future studies should focus on how to integrate higher-cognitive questions into Chinese college EFL classrooms.